2012
DOI: 10.1186/1476-511x-11-102
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil of the leaves of Ricinus communis L.: In vitro cytotoxicity and antimicrobial properties

Abstract: BackgroundThe aim of the present study was to appraise the antimicrobial activity of Ricinus communis L. essential oil against different pathogenic microorganisms and the cytotoxic activity against HeLa cell lines.MethodsThe agar disk diffusion method was used to study the antibacterial activity of Ricinus communis L. essential oil against 12 bacterial and 4 fungi strains. The disc diameters of zone of inhibition (DD), the minimum inhibitory concentrations (MIC) and the concentration inhibiting 50% (IC50) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…In this study, the Gram-negative isolates were less resistant to the plant extracts than the Gram-positive bacterial isolates. The higher resistance of Gram-negative bacteria could be accredited to the complexity of the double membrane including cell envelope, that be expressed by lipoprotein and lipopolysaccharide, and which plays the role of a barrier to the antibacterial substances, contrasted to the single membrane structure of Gram-positive bacteria (Zarai et al, 2012;Janakat et al, 2015). …”
Section: Effect Of Extracting Solvent On the Antimicrobial Activitymentioning
confidence: 99%
“…In this study, the Gram-negative isolates were less resistant to the plant extracts than the Gram-positive bacterial isolates. The higher resistance of Gram-negative bacteria could be accredited to the complexity of the double membrane including cell envelope, that be expressed by lipoprotein and lipopolysaccharide, and which plays the role of a barrier to the antibacterial substances, contrasted to the single membrane structure of Gram-positive bacteria (Zarai et al, 2012;Janakat et al, 2015). …”
Section: Effect Of Extracting Solvent On the Antimicrobial Activitymentioning
confidence: 99%
“…Anti-inflammatory (Lomash et al 2010;Srivastava et al 2014) with potential antimicrobial (Naz & Bano 2012) and anticarcinogenic properties of R. communis oil and potential use as natural remedy for topical treatment of infections (Zarai et al 2012). Castor oil polymer induces bone formation with high matrix metalloproteinase-2 expression (Saran et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…R. communis is well known for its biological activities, most important of which are hepatoprotective, laxative, antidiabetic, and antifertility activities [16]. Literature search revealed that essential oils from R. communis have been reported to have potential antimicrobial, anticarcinogenic, antioxidant, and antidiabetic activities [1719]. The aim of this study was to evaluate the cytotoxic effects of R. communis extracts against Human Caucasian skin fibroblast (BUD-8) cell line as well as its antioxidant activityusing 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) free radicals and anti-inflammation activity on the Raw 264.7 macrophages cell line.…”
Section: Introductionmentioning
confidence: 99%